2021
DOI: 10.1007/s43621-021-00040-z
|View full text |Cite
|
Sign up to set email alerts
|

The production of valuable products and fuel from plastic waste in Africa

Abstract: Global plastic waste generation is about 300 million metric tons annually and poses crucial health and environmental problems. Africa is the second most polluted continent in the world, with over 500 shipping containers of waste being imported every month. The US Environmental Protection Agency (EPA) report suggests that about 75% of this plastic waste ends up in landfills. However, landfills management is associated with high environmental costs and loss of energy. In addition, landfill leachates end up in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Common plastic wastes primarily include polyethylene (PE), polystyrene (PS), polyvinyl chloride (PVC), polyethylene terephthalate (PET), high-density PE (HDPE) and polypropylene (PP), and it is estimated that over 60% of plastic waste urban solids are composed of polyolefins, mainly low-density PE (LDPE), linear LDPE, HDPE, and PP [229]. Plastic waste from these polymers has complex mixtures of additives to configure specific properties in the final material, including, for example, thermal stabilizers, lubricating pigments, heat and light stabilizers, antioxidants, flame retardants and plasticizers [230,231]. The literature has reported that some of these additives have characteristics of endocrine-disrupting chemicals (EDCs), such as bisphenol A (BPA) and diethylhexyl phthalate (DEHP) [231], and these and other additives were classified as persistent contaminants [231].…”
Section: Accumulation Of Plastic Waste In the Environmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Common plastic wastes primarily include polyethylene (PE), polystyrene (PS), polyvinyl chloride (PVC), polyethylene terephthalate (PET), high-density PE (HDPE) and polypropylene (PP), and it is estimated that over 60% of plastic waste urban solids are composed of polyolefins, mainly low-density PE (LDPE), linear LDPE, HDPE, and PP [229]. Plastic waste from these polymers has complex mixtures of additives to configure specific properties in the final material, including, for example, thermal stabilizers, lubricating pigments, heat and light stabilizers, antioxidants, flame retardants and plasticizers [230,231]. The literature has reported that some of these additives have characteristics of endocrine-disrupting chemicals (EDCs), such as bisphenol A (BPA) and diethylhexyl phthalate (DEHP) [231], and these and other additives were classified as persistent contaminants [231].…”
Section: Accumulation Of Plastic Waste In the Environmentmentioning
confidence: 99%
“…Plastic waste from these polymers has complex mixtures of additives to configure specific properties in the final material, including, for example, thermal stabilizers, lubricating pigments, heat and light stabilizers, antioxidants, flame retardants and plasticizers [230,231]. The literature has reported that some of these additives have characteristics of endocrine-disrupting chemicals (EDCs), such as bisphenol A (BPA) and diethylhexyl phthalate (DEHP) [231], and these and other additives were classified as persistent contaminants [231]. As the content of additives in different waste products with different purposes can vary greatly, the chemical composition of recycled plastic is often unknown [232], which causes concern about the inappropriate disposal of this plastic waste into the environment, and the high degree of contamination, mainly in water bodies, with contaminants that are normally difficult to remove in conventional treatments.…”
Section: Accumulation Of Plastic Waste In the Environmentmentioning
confidence: 99%
See 3 more Smart Citations